2016
DOI: 10.1007/s12550-016-0261-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of ochratoxin A conjugates in urine samples from infants and adults

Abstract: Ochratoxin A (OTA), a mycotoxin with nephrotoxic and carcinogenic properties, is an important contaminant of food and feed. Analysis of OTA in human biological fluids (blood, urine, or breast milk) has documented frequent exposure to this mycotoxin, yet at quite variable levels in different population groups across the world. Urine is the preferred matrix in biomonitoring since sample collection is non-invasive and better accepted by study participants. As only a small fraction of the ingested OTA is excreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 54 publications
1
32
2
Order By: Relevance
“…High method sensitivity is of most importance since the concentration of these analytes in urine samples is often present in a very low concentration range. From the relatively few studies performed on one single mycotoxin in urine, OTA was the most common one, extracted from human urine by IAC [ 60 , 61 , 62 ], an automated multi-fiber SPME system [ 63 ], or the classical LLE with CHCl 3 -isopropanol [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…High method sensitivity is of most importance since the concentration of these analytes in urine samples is often present in a very low concentration range. From the relatively few studies performed on one single mycotoxin in urine, OTA was the most common one, extracted from human urine by IAC [ 60 , 61 , 62 ], an automated multi-fiber SPME system [ 63 ], or the classical LLE with CHCl 3 -isopropanol [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless OTA can be deactivated through sulphate and glutathione conjugation, which will lead to their secretion (Ringot et al 2006;Wu et al 2011). Recent studies demonstrated that ß-glucuronidase/arylsulfatase enzymatic hydrolysis of phase II metabolites returned significantly higher values for OTα in urine samples indicating that glucuronidation, and possibly sulfation, is involved in the detoxification process of OTα (Duarte et al 2011;Klapec et al 2012;Munoz et al 2017).…”
Section: Ochratoxin Amentioning
confidence: 99%
“…However, phase II metabolites of OTA were also observed in biological fluids such as urine, serum, and milk. Glucuronidated conjugates of OTA were more likely to be present in animal and human urine, as after enzymatic hydrolysis of the urine samples the levels of OTA and OTα were considerably (up to 6‐fold) higher (Muñoz, Cramer, Dopstadt, Humpf, & Degen, ; Pena, Seifrtova, Lino, Silveira, & Solich, ; Solfrizzo, Gambacorta, Lattanzio, Powers, & Visconti, ). Although there was clear evidence of OTA‐glucuronides, no glucuronidated forms have been identified yet.…”
Section: Ochratoxin Amentioning
confidence: 99%
“…Ochratoxin A‐8‐β‐glucuronide (OTA‐8‐glucuronide) and open lactone‐ochratoxin A‐8‐β‐glucuronide (open lactone OTA‐8‐glucuronide) have been synthesized as reference standards, but they have not been observed in human urine. Probably this phenomenon was attributed to a low sensitivity and ionization efficiency revealed in spiked analysis by LC‐MS/MS compared to OTA (Muñoz et al., ).…”
Section: Ochratoxin Amentioning
confidence: 99%